STRATEGI PENGELOLAAN LAHAN KRITIS - WIYONO WIYONO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2010)
Ready challenge of food progressively day progessively heavily.Degradation of Farm and envirenment , either by act of human being and alsonatural troble, progressively.